Newborn screening: knowledge and contributions of nursing team - Yriana Rodrigues Leal, Maria Helena Moura Pereira Neta, Silvana Santiago da Rocha (Revista de Enfermagem da UFPI)
DOI: https://doi.org/10.26694/reufpi.v2i1.831